Random polar sampling technique for the reliability analysis of submarine pressure hull - Radha, P; Rajagopalan, K (Journal of Naval Architecture and Marine Engineering, 2009)
Reliability analysis is essential to reduce the structural system failures to an acceptance level. In this paper, a quasi-Monte Carlo Simulation method called âRandom Polar Sampling Technique' (RPST) has been described for the reliability analysis of ring stiffened shell structure, in which the combinations of variates are obtained using a polar sampling of Latin hypercube sampled values. An efficient computer program coded in C++ has been developed for use with the RPST. Reliability analysis of internally ring stiffened submarine pressure hull has been described as an illustration and the results are compared with those given by First Order Second Moment method (FOSM), Advanced First Order Second Moment method (AFOSM) and Monte-Carlo Simulation methods. Keywords: Random Polar Sampling Technique, Reliability, Ring stiffened shells, Submarine pressure hull, Latin Hypercube Samples. Â doi: 10.3329/jname.v1i1.2036 Journal of Naval Architecture and Marine Engineering 1(2004) 26-34